2008
DOI: 10.1080/09585170801903225
|View full text |Cite
|
Sign up to set email alerts
|

From rhetoric to reality: advancing literacy by cross‐curricular means

Abstract: Cross‐curricularity, literacy and critical literacy are currently promoted as components of a curriculum appropriate for the twenty‐first century. The first two, in particular, are prescribed elements of classroom experience in Northern Ireland, which is the immediate context of this article, but also more widely in the UK. Teachers are implementing cross‐curricular and interdisciplinary initiatives, but rhetorical imperatives can translate into superficial realities. The reasons for this are explored, as are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 2 publications
0
8
0
2
Order By: Relevance
“…In contrast, their more skeptical colleagues made up a group of pure science teachers with two science subjects. Since the teachers researched in the study by Alexander et al (2008) showed a willingness to participate in such approaches and presented different ideas for doing so, it seems necessary to launch and carry out more projects like the one discussed here.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, their more skeptical colleagues made up a group of pure science teachers with two science subjects. Since the teachers researched in the study by Alexander et al (2008) showed a willingness to participate in such approaches and presented different ideas for doing so, it seems necessary to launch and carry out more projects like the one discussed here.…”
Section: Discussionmentioning
confidence: 95%
“…This position includes the idea that topics should not be too broad, but be more limited in scope (Palmer and Pettitt 1993;Barnes 2011) and that topics should have links which are natural, meaningful and purposeful and have conceptual coherence, rather than being tenuous and spurious (Martin 2002;Alexander et al 2008;Rowley and Cooper 2009). In addition, various authors have advocated that teachers should vary their planning approaches between whole class topic work, individual topics and modular units of work with a single curriculum focus, taking into consideration the context of the school and the children's specific needs.…”
Section: A Compromise Positionmentioning
confidence: 98%
“…He acknowledges the demands that cross-curricular teaching have on educators as it can often increase workload and challenges educators to embed something they may not be overly familiar with themselves (in this case, sustainability) into their own teaching and learning. This is reiterated by Alexander, Jarman, McClune, and Walsh (2008), who suggest that for teachers, ‘all too often, this could mean paying lip-service to the themes and making token gestures in their direction, with the substance of subject teaching remaining unaffected’ (p. 24).…”
Section: Context and Significancementioning
confidence: 99%